2021
DOI: 10.3390/medicina57020106
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Disseminated Intravascular Coagulation in a Patient with COVID-19 and Associated Sepsis—Induced Neutropenia

Abstract: COVID-19 has been associated with a hypercoagulable state and thrombotic events. Venous thromboembolism has been the most commonly reported type of thrombosis but also arterial thrombosis and disseminated intravascular coagulation in inpatients have been described frequently in several clinical experiences. Patients with COVID-19, because of its tendency to induce leucopenia and overlapping of bacterial infection, may experience sudden disseminated intravascular coagulation (DIC), as in the case that we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Bacterial superinfection is common in COVID-19 9 and attributed to neutropenia due to sepsis or a weak humoral immune response. 10 DIC syndrome in the context of COVID-19 has been also attributed to sepsis. 10…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial superinfection is common in COVID-19 9 and attributed to neutropenia due to sepsis or a weak humoral immune response. 10 DIC syndrome in the context of COVID-19 has been also attributed to sepsis. 10…”
Section: Discussionmentioning
confidence: 99%
“…The preceding considerations along with direct evidence of bacterial infections in non‐COVID thrombocytopenias [ 76 , 77 ] and some COVID‐19 coagulopathy cases [ 78 , 79 , 80 , 81 ] have led Di Micco et al. [ 82 ] to conclude that, “Patients with COVID‐19, because of its tendency to induce leucopenia and overlapping of bacterial infection, may experience sudden disseminated intravascular coagulation (DIC).”…”
Section: Discussionmentioning
confidence: 99%
“…Other evidence of bacterial co-infections in severe COVID-19 are the presence of elevated ferritin, [70,71] C-reactive protein, [71][72][73][74] procalcitonin levels, [71,74] as well as eosinopenia and lymphopenia [74,75] and cytokine overproduction syndrome (reviewed in [69] ), all of which are independently diagnostic for bacterial infections and differentiate severe cases from mild and asymptomatic ones. The preceding considerations along with direct evidence of bacterial infections in non-COVID thrombocytopenias [76,77] and some COVID-19 coagulopathy cases [78][79][80][81] have led Di Micco et al [82] to conclude that, "Patients with COVID-19, because of its tendency to induce leucopenia and overlapping of bacterial infection, may experience sudden disseminated intravascular coagulation (DIC). "…”
Section: Probable Roles Of Bacteria In Triggering Covid-19 Coagulopathiesmentioning
confidence: 99%
“…), etc., which revealed that some of the most common autoantigen targets in COVID-19-associated coagulopathies, such as CL, PF4 and β2GP, have significant mimics with these bacteria but do not have significant mimics with SARS-CoV-2 and especially its spike protein [ 40 ] (summarized in Figure 1 ). Since some bacterial infections, especially GAS , Staphylococci, Klebsiella and Clostridia , are themselves associated with increased risks of coagulopathies [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], these results suggested that preceding or concomitant bacterial co-infections may support the induction of a variety of COVID-19 autoimmune coagulopathies through anamnestic secondary cross-reactivity or bystander activation of complementary autoimmune mechanisms to those activated by SARS-CoV-2. Conversely, if a pre- or co-existing bacterial infection were necessary to induce autoimmune coagulopathies, then the absence of such infections among the vast majority of vaccinees might explain the extremely infrequent occurrence of vaccine-induced thrombotic events [ 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%